Calappa galloides Stimpson 1859 ... - In, First Published (Zenodo, 2022)
Calappa galloides Stimpson, 1859 (Fig. 10A–E) Calappa galloides Stimpson, 1859: 71 [Type locality: Florida Keys]. Trindade specimens. 1 juvenile male (MZUSP 33818), Brazil, off Espírito Santo, Trindade Island, Ponta da Calheta, 20°30’18.72”S, 29°18’31.67”W, J.B. Mendonça coll., 22.x.2014, 15.8 m. 1 male (MZUSP 33815), ibidem, 4.viii.2015, tangle net set over the bottom, 15.8 m. Size of largest male: cl 28 mm, cw 38 mm. Comparative material examined. Calappa galloides: Panama: 1 male (USNM 43996), Caribbean Sea, Colón, Limon Bay, coral reef, M. Hildebrand coll., 2.v.1911 [M. J. Rathbun det.]. Brazil: Paraíba: 1 male (MZUSP 5921), Projeto Algas, stn 12C, 7°28’S, 34°34’W, 6.v.1981, 30 m. 1 male (MZUSP 5932), ibidem, stn 29D, 7°15’S, 34°36’W, 2.iv.1981, 28 m. Bahia: 1 male (MZUSP 41411), Minerva Seamount, 17°03.108’S, 37°37.216’W, J. Coltro coll., 12.viii.2012, 69 m. Espírito Santo: 1 male (MZUSP 8018), Serra, Jacaraípe, J.L. Helher coll., iii.1973. Rio de janeiro: 1 female (MZUSP 9428), Ilha Grande, 105 m. São ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on pages 23-24, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...